Interplay among IncA and bla(KPC)-Carrying Plasmids in Citrobacter freundii - Bitar, Ibrahim (Antimicrob Agents Chemother, 2019)
We report two KPC-producing Citrobacter freundii isolates from unrelated patients. In one case, bla(KPC-2) was harbored on a novel variant of a Tn4401 transposon of an IncN plasmid conjugated together with a coresident IncA plasmid, whereas in the other one, bla(KPC-3) was on a Tn4401a transposon located on an IncX3-IncA self-conjugative plasmid fusion. The interplay among plasmids carrying bla(KPC) and the coresident IncA plasmids offers new information on plasmids coresident within clinically relevant enterobacteria.